PERTANGGUNGJAWABAN PIDANA PENGIRIM SHORT MESSAGE SERVICE (SMS) PORNOGRAFI BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Hartika Sari, Juniar (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
The more people use technology, the world of information today seems impossible to get rid of. Communications that used to take a long time can now be done very quickly and easily thanks to technology. Is pornography caused by SMS. There are several factors that can cause pornography to be sent through the Short Message Service (SMS): enabling the perpetrators of the sex service and the users of such a fast-paced pornographic service because of the highly lucrative pornographical industry. Applications on the Internet can be used to do online prostitution without going through and involving Germo or Mucikari. Sex service transactions are more practical and effective. By checking in in person and meeting at hotels, the practice of prostitution is safer.